Mathematics OpenStudy (anonymous):

Write the equation of the parabola that has a vertex (1, -1) and passes through the point (2,5) OpenStudy (accessdenied):

Do you know the "vertex form" of a quadratic equation? OpenStudy (anonymous):

no OpenStudy (accessdenied):

Vertex Form: \( y - k = a(x - h) \) Although some people learn it as standard form. I learned it as "Vertex form" though. If we use that form, the vertex can be put in as (h,k) = (1,-1) Then, we just have to find a by using the given point as the values for (x,y), and solving for a. OpenStudy (anonymous):

what did u get OpenStudy (accessdenied):

y - (-1) = a(x - 1) <== (x,y) = (2,5) y + 1 = a(x - 1) 5 + 1 = a(2 - 1) 6 = a y + 1 = 6(x - 1) y = 6(x-1) - 1 But, if you don't know vertex form, I think we could also use \(ax^2 + bx + c = y\) and some relations of the coefficients... OpenStudy (accessdenied):

Yeah. y = ax^2 + bx + c We can create a system of equations using the two points and a relation between the vertex and the coefficients. 5 = a(2)^2 + b(2) + c ==> 5 = 4a + 2b + c } System -1 = a(1)^2 + b(1) + c ==> 1 = a + b + c } -b/2a = 1 (x-value of vertex is -b/2a) -b = 2a b = -2a Substitute into the system to eliminate (b) 5 = 4a + 2(-2a) + c -1 = a + (-2a) + c 5 = 4a - 4a + c -1 = a - 2a + c 5 = c --, Substitute C -1 = -a + c -1 = -a + 5 -6 = -a a = 6 ==> b = -2(6) = -12 y = 6x^2 -12x + 5 OpenStudy (accessdenied):

Which, if we compare with the vertex-form equation, is the same if we expand the binomial and distribute/ simplify: y = 6(x - 1)^2 - 1 = 6(x^2 - 2x + 1) - 1 = 6x^2 - 12x + 6 - 1 = 6x^2 - 12x + 5

Latest Questions Noodlearms: I'll take a screenshot of the question and post it below my question as a response.
3 hours ago 1 Reply 0 Medals Ginnygine: Hang Yo bought a treadmill for \$875. He made a 20% down payment and financed the rest over 24 months.
3 hours ago 0 Replies 0 Medals Yuri: The high temperature on Friday was 8 degrees above zero. The low temperature was 3 degrees below zero.
3 hours ago 0 Replies 0 Medals Daddysdfff: Which of the following is an accurate statement about vectors? A. Rotating a vector about an axis is passing through the tip of the vector does not change t
3 hours ago 4 Replies 0 Medals babygirlcuhh: All praise is due to ALLAH alone, Lord of all the worlds... THEE alone do we worship and THEE alone do we implore for health.
4 hours ago 2 Replies 0 Medals BBlove2020: Which colonial group was formed first? (5 points) First Continental Congress Comm
5 hours ago 0 Replies 0 Medals doosii: What is the mass in grams of KBr in 0.400 L of a .350 M solution?
5 hours ago 0 Replies 0 Medals hannahcarrafa045: Dependent variables can be the result of more than one independent variable. Consider your phone bill as presented in the Opening Activity.
5 hours ago 0 Replies 0 Medals KIYAMAYQXW: Marlena created a table of values u200bu200brepresenting the height in feet, h ( t ), of a coconut falling to the hard ground with a height of 0 feet, colle
6 hours ago 0 Replies 0 Medals Greatkitty2418: A society in the near future values education and career over family more and mor
6 hours ago 0 Replies 0 Medals